DENSITY AND DIVERSITY OF SEAWEED IN WEDA BAY WATERS, NORTH MOLLUCAS PROVINCE - Hairati Arfah; Saleh Papalia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The study on seaweed density and diversity in many substrates was conducted in Weda Bay waters, North Mollucas in 2013. The objectives of this research was to determine the density and diversity of seaweed in many different substrates and to determine the relationship of substrate types and seaweed density and diversity in Weda Bay waters. Data were collected using quadrate transect method and collections. The result showed that the coastal area of Batlol, Weda Bay contained higher density and diversity of macroalgae than other locations with 35 species of 24 families consisting of 14 species of red macroalgae, 12 species of green algae, and 9 species of brown algae. The dominan families of macroalgae were Gracilaria, Acanthophora, Caulerpa, Halimeda, Sargassum, and Turbinaria. The dominant difference of macroalgae in each location was caused by differences in habitat type, e.q., habitat in Batlol consisted of fragments of dead coral, sand, little living coral with vegetation seaweed that dominated by Thalasia hemprizii and Symodacea rotundata. While habitat conditions at other locations experienced severe damage that dominated by chunks of dead coral, dead coral rubble, and sand. Environmental conditions in study regions were considered to be in a good condition to support macro-algae growth.Keywords: seaweed, macro algae, substrate, density, diversity, Weda Bay